2020
DOI: 10.1002/bse.2565
|View full text |Cite
|
Sign up to set email alerts
|

Does eco‐innovation drive sales and technology investment? Focusing on eco‐label in Korea

Abstract: As environmental problems worsen, eco-innovation research has received increased attention. Korea is implementing an eco-label policy to induce eco-innovation. Eco-labeling is a type of voluntary eco-innovation. There are few empirical studies on the economic performance of eco-labels in Korea and even fewer on the additional investment in the technology used for eco-labeling. The present study quantitatively measured the effect of eco-labels on additionally generated sales and research and development (R&D) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 55 publications
(75 reference statements)
6
32
0
Order By: Relevance
“…Eco-innovations not only entail environmental benefits, but also are a source of competitiveness for firms (Porter and Linde 1995;Demirel and Kesidou 2011;García-Sánchez et al 2020a). Indeed, several studies have showed that successful environmental innovations allow companies to diminish costs and risks (Hart and Ahuja 1996;Ambec and Lanoie 2008), increase sales and market share both in current markets and in new markets (Kim et al 2019;Oh et al 2020), improve stakeholder relationships and firm reputation (Brammer and Pavelin 2006;Cheng and Shiu 2012), and enhance productivity and margins (Sammer and Wüstenhagen 2006;Ruben et al 2009;Ruben and Fort 2012), among other competitive benefits. To the extent that the overall benefits exceed the costs and risks involved, eco-innovations will have a positive impact on financial performance (Long et al 2017).…”
Section: Environmental Innovation and Financial Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Eco-innovations not only entail environmental benefits, but also are a source of competitiveness for firms (Porter and Linde 1995;Demirel and Kesidou 2011;García-Sánchez et al 2020a). Indeed, several studies have showed that successful environmental innovations allow companies to diminish costs and risks (Hart and Ahuja 1996;Ambec and Lanoie 2008), increase sales and market share both in current markets and in new markets (Kim et al 2019;Oh et al 2020), improve stakeholder relationships and firm reputation (Brammer and Pavelin 2006;Cheng and Shiu 2012), and enhance productivity and margins (Sammer and Wüstenhagen 2006;Ruben et al 2009;Ruben and Fort 2012), among other competitive benefits. To the extent that the overall benefits exceed the costs and risks involved, eco-innovations will have a positive impact on financial performance (Long et al 2017).…”
Section: Environmental Innovation and Financial Performancementioning
confidence: 99%
“…The study of the effect of eco-innovation on financial performance has received considerable attention in the literature, although empirical results are not conclusive existing two opposite trends (Przychodzen and Przychodzen 2015;Alos-Simo et al 2020;Oh et al 2020). The majority of empirical evidence documents a positive association between eco-innovation and financial performance (Hojnik et al 2018).…”
Section: Environmental Innovation and Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The promotion effect of green finance on ecological innovation has been extensively confirmed, including on green technology innovation (Chassagnon and Haned, 2015) and green patents (Marin-Vinuesa et al, 2020), the R and D investment (Costa-Campi et al, 2017;Oh et al, 2020), as well as financial performance (Duque-Grisales et al, 2020;Xiang et al, 2020). Jones (2015) pointed out that sustainable finance and green finance encouraged investment in new technologies and innovations, which include renewable energy technologies.…”
Section: The Intermediary Effect Of Green Technology Innovationmentioning
confidence: 96%
“…Secondly, we add to the understanding of the economic impact of environmental innovations by showing the effect of eco-product innovations on sales growth. Although the contribution of environmental innovations to business performance has been extensively analyzed (Przychodzen and Przychodzen 2015;Oh et al 2020), prior research obtained no conclusive results (Hojnik et al 2018). A possible explanation could be the use of different proxies of firm performance (e.g., ROI, profitability, operating profit).…”
Section: Introductionmentioning
confidence: 99%